2018
DOI: 10.3390/atmos9020038
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Dispersion Modelling and Spatial Analysis to Evaluate Population Exposure to Pesticides from Farming Processes

Abstract: This work originates from an epidemiological study aimed to assess the correlation between population exposure to pesticides used in agriculture and adverse health effects. In support of the population exposure evaluation two models implemented by the authors were applied: a GIS-based proximity model and the CAREA atmospheric dispersion model. In this work, the results of the two models are presented and compared. Despite the proximity analysis is widely used for these kinds of studies, it was investigated how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…We included sex and age as potential confounders and effect-modifiers in a multivariable model. We further adjusted for residential passive exposure to pesticides as assessed using proximity to agricultural land use [37][38][39] or inorganic selenium species [26]. We used 'logit', 'mkspline', and 'xblc' routines of the Stata 16.1 (Stata Corp., College Station, TX, USA) for all statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We included sex and age as potential confounders and effect-modifiers in a multivariable model. We further adjusted for residential passive exposure to pesticides as assessed using proximity to agricultural land use [37][38][39] or inorganic selenium species [26]. We used 'logit', 'mkspline', and 'xblc' routines of the Stata 16.1 (Stata Corp., College Station, TX, USA) for all statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A large majority used GIS to calculate spatial surrogates for pesticide exposure and a minority PLOS ONE employed surveys to estimate residential distance from the first fields. Only two studies used a dispersion model to assess concentrations in the vicinity [35,36]. The predominant use of GIS could be explained by the relative simplicity of these tools and the possibility of applying them to a data set including many observations [37].…”
Section: Assessment Of Residential Exposure In Epidemiological Studiesmentioning
confidence: 99%
“…In the selected studies, GIS were generally used to define buffers around the residential location, assuming an isotropic distribution of the pesticide emissions into the atmosphere, without integrating meteorological data. One study we selected in our scoping review showed that this can result in an underestimation of populations living downwind and overestimations of residents living upwind of the treated areas [35]. Unlike GIS, dispersion models are deterministic models, based on atmospheric diffusion and reaction equations that can take into account the anisotropic distribution of the aerial dispersion of pesticides.…”
Section: Assessment Of Residential Exposure In Epidemiological Studiesmentioning
confidence: 99%
“…Modena is located in the north of Italy, along the "via Aemilia", an ancient Roman road running from Rimini to Piacenza on the river Po ( Figure 2). The Po Valley is characterized by a high population density and by processes of industrialization and intensive agriculture (it is among the most productive agricultural areas within Europe) [72]. The climate of this region is partially continental: summers are hot with intense heat waves while winters are cold and wet, usually with atmospheric stability conditions and fog.…”
Section: Study Areamentioning
confidence: 99%
“…Normally precipitation is concentrated during autumn and spring. Summer and winter are the driest seasons [57,58,72,73]. In order to have a clear climate situation of the study area, Table 1 reports some climate information.…”
Section: Study Areamentioning
confidence: 99%